Next Generation Funds ( EU, Conceptual and Analytical Approaches) - Cicuéndez Santamaría, Ruth (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The purpose of this entry is to define and analyze the Next Generation EU (NGEU) funds, an extraordinary financial mechanism created by the European Union in response to the crisis resulting from the pandemic. The primary objective of this novel instrument is twofold: firstly, to promote economic recovery in the short term, and secondly, to achieve a structural transformation of the European economic model in the long term. The article provides a detailed analysis of the NGEU’s characteristics, highlighting its substantial financial allocation, exceptional nature, temporariness, conditionality, and solidarity. The article also examines how this mechanism is generating a new glossary in the EU’s budgetary policy, introducing terms such as resilience, national recovery plans, or milestones and targets, which are redefining the conceptual framework of European structural financing. Finally, the article addresses the impact of NGEU on multi-level governance and discusses its potential to shape a new paradigm for crisis management and European fiscal integration. The conclusion drawn is that NGEU funds are not merely a financial instrument; rather, they constitute an economic and political pact with long-term implications.